Challenges of Learning Islamic Cultural History for Generation Alpha from a Cross-Cultural Communication Perspective - Hanifah Nur Inayah; Fitriyani Ramadhan; Faiha Nur Haya; Amelia Khoirunisa; Afiyatun Kholifah (Annujum: Journal of Humaniora and Law, 2026)
The development of digital technology has brought changes to the learning patterns and communication styles of students in the modern era. Generation Alpha, as a generation that grew up alongside technology, has distinct characteristics compared to previous generations, particularly in how they receive information, interact, and understand learning. This situation presents unique challenges in teaching Islamic Cultural History (ISH), especially when the learning process still uses conventional methods that are less suited to the characteristics of students in the digital age. On the other hand, ISH learning plays a crucial role in instilling values of tolerance, religious moderation, and respect for cultural diversity in social life. This study aims to examine the challenges of ISH learning for Generation Alpha from a cross-cultural communication perspective. The study employed a literature study method (library research) with a descriptive qualitative approach through a review of various scientific journals, research articles, and other sources relevant to the research topic. The results indicate that differences in communication patterns, digital culture, and learning characteristics of Generation Alpha require more adaptive, interactive, and communicative ISH learning strategies. A cross-cultural communication approach in ISH learning is considered relevant for developing a tolerant, open, and respectful attitude toward differences in a multicultural society. Therefore, Islamic Education (IS) learning needs to be developed through the use of digital media and contextual learning approaches so that Islamic historical values can be more effectively understood by Generation Alpha.